Efficacy of Voriconazole in a Guinea Pig Model of Invasive Trichosporonosis - Serena, Carolina (American Society for Microbiology, 2006)
We have evaluated the efficacy of voriconazole (VRC) in a systemic infection by Trichosporon asahii in immunosuppressed guinea pigs. VRC was more effective than amphotericin B in prolonging survival and reducing tissue burden. The best results were obtained with VRC at 10 mg/kg of body weight/day.